Drugs Consumer Protection in a Global Age - Csorba, Luiela-Magdalena (Mediterranean Journal of Social Sciences, 2011)
The United States food and drug laws provide the highest level of consumer protection in the world. But, instead of thehuge number of legal measures taken by governments to eradicate this scourge, drugs consumer protection remains a fieldwhich still have a lot of unsolve problems, all around the world: in Europe, Asia, Afrika and so on.